A Jewish childhood in the Muslim Mediterranean : a collection of stories curated by Leïla Sebbar - Sebbar, Leïla; Brozgal, Lia Nicole, 1972-; Brozgal, Lia Nicole, 1972-; Glasberg, Rebecca, 1986-; Kuntz, Jane; Vince, Rebekah; Watson, Robert J. (Robert Jay), 1983- (University of California series in Jewish history and cultures, 2023)
"A free ebook version of this title is available through Luminos, University of California Press's Open Access publishing program. Visit www.luminosoa.org to learn more. A Jewish Childhood in the Muslim Mediterranean brings together the fascinating personal stories of Jewish writers, scholars, and intellectuals who came of age in lands where Islam was the dominant religion and everyday life was infused with the politics of the French imperial project. Prompted by novelist Leïla Sebbar to reflect on their childhoods, these writers offer up a set of literary portraits that gesture to a universal condition while also shedding light on the exceptional nature of certain experiences. The childhoods captured here are undeniably Jewish, but they are also Moroccan, Algerian, Tunisian, Egyptian, Lebanese, and Turkish; each essay thus testifies to the multicultural, multilingual, and multi-faith communities into which its author was born. This translation makes this unique collection of essays available to a broad anglophone public for the first time. The original version, published in French in 2012, was awarded the Prix Haïm Zafrani, a prize given by the Elie Wiesel Institute of Jewish Studies to a literary project that valorizes Jewish civilization in the Muslim world"--